Biological functions of Elabela, a novel endogenous ligand of APJ receptor. Issue 9 (25th March 2018) - Xu, Jin; Chen, Linxi; Jiang, Zhisheng; Li, Lanfang
Abstract : The G protein‐coupled receptor APJ and its cognate ligand, apelin, are widely expressed throughout human body. They are implicated in different key physiological processes such as angiogenesis, cardiovascular functions, fluid homeostasis, and energy metabolism regulation. Recently, a new endogenous peptidic ligand of APJ, named Elabela, has been identified and shown to play a crucial role in embryonic development. In addition, increasing evidences show that Elabela is also intimate associated with a large number of physiological processes in adulthood. However, a comprehensive summary of Elabela has not been reported to date. In this review, we provide an overview of the biological functions of Elabela. Collectively, Elabela, a potential therapeutic peptide, exerts diverse biological functions in both embryos and adult organisms, such as dysontogenesis, self‐renewing of human embryonic stem cells, endoderm differentiation, heart morphogenesis, cardiac dyfunctions, blood pressure control, angiogenesis, blood pressure control, regulation of food and water intake, bone formation, and kidney diseases. Abstract : Recently, a new endogenous peptidic ligand of APJ, named Elabela, has been identified and shown to play a crucial role in embryonic development and a large number of physiological processes in adulthood. However, a comprehensive summary of Elabela has not been reported to date. In this review, we provide an overview of the biological functions of Elabela in both embryos and adult organisms, such as dysontogenesis, self‐renewing of human embryonic stem cells, endoderm differentiation, heart morphogenesis, cardiac dyfunctions, blood pressure control, angiogenesis, blood pressure control, regulation of food and water intake, bone formation, and kidney diseases.